The territory into architecture. Big scale and agriculture in Italian Architecture, 1966-1978 - Zeila Tesoriere (Agathón)
An unprecedented inter-scalarity links Italian Architecture to the notion of territory between 1966 and 1978. Two main strands are shown as theoretical foundations of some contemporary orientations of the discipline. The first refers to Vittorio Gregotti and Aldo Rossi, the second to the Radical Avant-garde. The teaching of the territory concerning the modalities of relationship between formal facts and the autonomous role of architecture in the historical city, seen in parallel with the fictional projects of the Radical Architecture and the role that agriculture plays there, shows that trans-scalarity is here inseparable from trans-disciplinarity. Those works, distilling the formal gesture to reactivate large-scale relationships in a diachronic time, by opposing architecture to the artificiality of the consumerist city on its way to conquest every land, using the collage in a poetics for fragments, and composing projects as scenarios, still echo in our season.